1989
DOI: 10.1101/gad.3.8.1255
|View full text |Cite
|
Sign up to set email alerts
|

A developmental-specific factor binds to suppressor sites flanking the immunoglobulin heavy-chain enhancer.

Abstract: We identified a novel nuclear protein, NF-|jiNR, that binds to multiple sites flanking the immunoglobulin heavy-chain enhancer. The expression of NF-|jiNR shows a unique developmental pattern; the activity is present in all cells representing early stages of B-cell development, but is absent from more mature cells that express a high level of immunoglobulin heavy chains. NF-|iNR also is present in most cell lines outside of the B-cell lineage (e.g., T cells, macrophages, and fibroblasts). The binding sites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 56 publications
7
85
0
Order By: Relevance
“…Because CDP has a stronger affinity for these sites than the activator protein, binding of CDP prevents binding of the activator, thus leading to repression of gene expression. Although most of these activators are not known, recent results suggest that immunoglobulin heavy-chain transcription may be, in part, restricted to B cells through the binding of B-cell-specific activators, such as Bright (30), that accompany the decreasing levels of CDP repressor present during B-cell differentiation (56). The identities of activators that bind to MMTV LTR sites occupied by CDP during mammary gland differentiation are unknown.…”
Section: Fig 8 Stable Transfections Of Mmtv Ltr-reporter Gene Constmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CDP has a stronger affinity for these sites than the activator protein, binding of CDP prevents binding of the activator, thus leading to repression of gene expression. Although most of these activators are not known, recent results suggest that immunoglobulin heavy-chain transcription may be, in part, restricted to B cells through the binding of B-cell-specific activators, such as Bright (30), that accompany the decreasing levels of CDP repressor present during B-cell differentiation (56). The identities of activators that bind to MMTV LTR sites occupied by CDP during mammary gland differentiation are unknown.…”
Section: Fig 8 Stable Transfections Of Mmtv Ltr-reporter Gene Constmentioning
confidence: 99%
“…However, it is an attractive possibility that CDP binding sites could be used to isolate proteins that activate transcription following the loss of CDP binding activity that accompanies differentiation of the mammary gland. Because the loss of CDP occurs in a number of differentiating cell types (1,56,57), this strategy also may be applicable to the isolation of transcriptional activators in other tissues.…”
Section: Fig 8 Stable Transfections Of Mmtv Ltr-reporter Gene Constmentioning
confidence: 99%
“…In the IgH locus, the intronic E enhancer is flanked on both sides by intimately associated MARs (24). In B cells, they are associated with MAR-BP1 and Bright (39,52), whereas in non-B cells they are bound by SATB1 and NF-NR which is likely Cux/CDP (28,53). 3 Similarly, MAR ␤ is just 400 bp upstream of E ␤ and is also associated with Cux/CDP and SATB1.…”
Section: Figmentioning
confidence: 99%
“…In the immunoglobulin heavy chain (IgH) locus, MARs flank the intronic enhancer E and are in close proximity to V H promoters (22)(23)(24)(25)(26). Reporter gene assays in cell lines and transgenic mice have suggested that these MARs exert both positive and negative effects on IgH gene transcription and promote long range chromatin accessibility (27)(28)(29)(30)(31). A highly conserved MAR is also found 200 base pairs (bp) upstream of the intronic immunoglobulin (Ig) enhancer in mouse, human, and rabbit (22,32).…”
Section: Cd8mentioning
confidence: 99%
“…It has been reported that RAG-2 is not expressed naturally in mature lymphocytes [4,10]. The abnormal expression maybe implies that Ep needs to associate with an additional flanking region, such as a matrix attachment region, for its correct regulation in vivo [27,28]. Alternatively, Ep may have to interact with another negative regulatory element, such as a silencer, to specifically prevent its activation in mature B cells.…”
mentioning
confidence: 99%